Phytochemical screening and antibacterial activity of Caesalpinia bonduc (Linn.) Roxb root bark extracts as a potential source for natural dyes. - Omar Al-Abdalla, Sahar Varona (2013.)
Plants have been used traditionally for common human ailments for many years due to their antimicrobial properties. The anitmicrobial properties of these plant extracts are being evaluated scientifically and explored to their potential as antimicrobial agents when incorporated in textiles as natural dyes. Toxins in synthetic dyes have been found to be carcinogenic, thus, there is a growing worldwide concern for eco-friendly substitutes. Since natural dyes take on a more eco-friendly approach, this study explored the phytochemical and antimicrobial properties of Caesalpinia bonduc root bark to determine its potential as a source for natural dyes. Phytochemical screening tests were performed on crude methanol extracts of the root bark and were further tested using TLC techniques. An antimicrobial assay was performed using Kirby-Bauer disc diffussion method against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and bacillus cereus. Results from phytochemical analysis showed the presence of cardiac glycosides, saponins, tannins, flavonoids and flavanol glycosides. Results of the antimicrobial assay showed weak effects against E. coli, P. aeruginosa adn S. aureus while B. cereus was resistant.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Caesalpinia bonduc -- Natural Dyes